2017
DOI: 10.1002/bsl.2325
|View full text |Cite
|
Sign up to set email alerts
|

Gender and mental health: An examination of procedural justice in a specialized court context

Abstract: The procedural justice framework has been applied in the criminal justice contexts of policing, corrections, and courts. According to this perspective, fair treatment, respectful dialogue and being given a proper voice will contribute to citizens' positive views of authority figures. While this literature has grown immensely, several questions remain unanswered. Do males and females perceive similar levels of procedural justice? Does mental health status influence perceptions of fair treatment? Whether procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…Conversely, procedural justice concerns the assessment of the fairness of procedures, centering on interpersonal treatment within the CJS (Lucas et al 2011). The exact criteria needed to achieve procedural justice in court is debated; however, the four main principles used to assess justice institutions include voice, neutrality, respect, and trust (McKenna and Holtfreter 2020; Somers and Holtfreter 2017;Tyler and Jackson 2014;Tyler and Lind 1992). Literature supports the notion that individuals judge outcomes and procedures in relation to specific contexts and Just World Beliefs about society that arise from a need to see the world as fair (and just) (Lerner 1980;Lucas et al 2007).…”
Section: Justice Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, procedural justice concerns the assessment of the fairness of procedures, centering on interpersonal treatment within the CJS (Lucas et al 2011). The exact criteria needed to achieve procedural justice in court is debated; however, the four main principles used to assess justice institutions include voice, neutrality, respect, and trust (McKenna and Holtfreter 2020; Somers and Holtfreter 2017;Tyler and Jackson 2014;Tyler and Lind 1992). Literature supports the notion that individuals judge outcomes and procedures in relation to specific contexts and Just World Beliefs about society that arise from a need to see the world as fair (and just) (Lerner 1980;Lucas et al 2007).…”
Section: Justice Attitudesmentioning
confidence: 99%
“…Some research has also found public support for procedural justice frameworks being introduced into courts (Somers and Holtfreter 2017;Watson 2021). A review of the 2011 CSEW demonstrates that procedural fairness principles, namely respect and voice, remain key to ensuring public legitimacy (Hough et al 2013).…”
Section: Justice Attitudesmentioning
confidence: 99%
“…It is possible that courts, which are designed to give laypeople voice either as litigants or jurors, foster fairness (Hamm 2019;Machura 2003). More recent research focusing on specialized, problem-solving courts, for instance, has found that defendants in drug courts and community courts report higher levels of procedural fairness, which reflects the less adversarial, more deliberative design of these settings (Connor 2019;Somers and Holtfreter 2018, see also Dollar, et al 2018;Atkin-Plunk and Armstrong 2016;McIvor 2009).…”
Section: Literature Review Procedural Fairness and Legal Institutionsmentioning
confidence: 99%